The Design Method of Traction Power Supplies in Integrated Metro Systems - Doan Van, Dong; Thai, Nguyen (Engineering, Technology & Applied Science Research, 2023)
Integrated subway systems have emerged as a new trend that provides the highest quality service at the lowest investment cost by combining the advantages of the two largest passenger transport capabilities during peak hours. Under the integrated model, designing the traction power supply is much more complex than for other independent systems. This article presents the results of a study on the method of calculating the design load of the power supply for the transport operation of the system. Matlab R2017b/Railway Systems is a reliable software for simulating and analyzing some necessary data, and the research results show the feasibility of the method when applied to the case of asynchronous load on the system. The results meet the power supply design standards according to IEEE P1653.2, EN 50328, and IEC 60146-1 overload allowances for class VI, and voltage standards according to EN 50163, UIC 600, and IEC 60850.